ANALYSIS OF SCHOOL PRINCIPALS' MANAGERIAL COMPETENCE IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN ELEMENTARY SCHOOLS - Fatimah Fatimah; Ruslaini Ruslaini; Sumarno Sumarno (Jurnal Cakrawala Pendas, 2025)
The implementation of the Merdeka Curriculum in elementary schools requires school principals to possess adequate managerial competencies to manage changes in a more flexible learning system that is based on students' needs. The managerial competencies of school principals play a key role in the successful implementation of educational policies, including the Merdeka Curriculum, which emphasizes flexibility, differentiated learning, and independent learning. This study aims to analyze the managerial competencies of school principals in the implementation of the Merdeka Curriculum in elementary schools in Central Aceh Regency. The research method used is a qualitative descriptive approach with data collection techniques through questionnaires, observations, and interviews. The subjects of the study consist of school principals and teachers from nine elementary schools in Central Aceh Regency. The results indicate that school principals have adequate managerial competencies in managing schools, covering the stages of planning, organizing, implementing, supervising and evaluating, decision-making, and leadership in educational innovation. However, there are still several competencies that need improvement, particularly in the execution of administrative management and documentation aspects required to ensure that all students benefit optimally and to facilitate changes in student-centered learning methods by the principles of the Merdeka Curriculum. This study recommends enhancing training and support for school principals in the implementation of the Merdeka Curriculum. Thus, the improvement of managerial competencies among school principals is expected to support the successful implementation of the Merdeka Curriculum in elementary schools.